Azoles Synthesis, Properties, Applications and Perspectives - Kuznetsov, Aleksey (IntechOpen, 2021)
Azoles are a broad and promising class of five-membered heterocyclic compounds containing from one up to five nitrogen atom(s) that can also contain sulfur or oxygen atoms. Widely used as potent antifungal agents, various azole derivatives have also demonstrated many other promising biological properties. This book covers studies of several types of thiazole-based heterocyclic scaffolds, the development of 4-thiazolidinone and thiazole derivatives with heterocyclic fragments as potential candidates for new drugs against trypanosomiasis, numerous synthetic approaches for the synthesis of 1,2,3-triazoles, the application of N-azole, N,S-azole, and N,O-azole as well as their derivatives as retarders of metallic corrosion, and the integration of azoles in materials used for renewable energy processing and applications and wood treatment.